Factors Influencing the Adoption of Electronic Commerce Among the Small and Medium Sized Enterprises in Australia - Chong, Sandy; Ramaseshan, Balasubramanian (NIILM Center for Management Studies, 2005)
This study surveys the perceptions and experiences of Australian small- and medium-sized enterprises (SMEs) in the adoption of Electronic Commerce (EC) and proposes a framework of EC adoption for SMEs. This study shows that Australian SMEs were very receptive to adopting EC. A multiple regression analysis shows that eight factors: age of firm, complexity, compatibility, communication channel, communication amount, customer pressure, competitive pressure, and perceived governmental support significantly influence the adoption of EC by SMEs in Australia. The managerial implications are discussed.